Permanent land use and microbial contributions shape soil organic carbon stabilization in lake floodplains - Toky Jeriniaina Rabearison; Jim Félix-Faure; François Guillemette; Michelle Garneau; Christine Martineau; Louis Astorg; Martin Chantigny; Virginie Favreau; Jessika Malko; Alexandre Roy; Vincent Maire (Soil Biology and Biochemistry, 2026)

Unravelling the ketone story. Secondary vessel use at the Ness of Brodgar, Orkney, Scotland - Julia Becher; Alexandre Lucquin; Rowan McLaughlin; Martine Regert; Mark Edmonds; Jan Blatchford; Nick Card; Anne Mitchell; Helen M. Talbot; Roy Towers; Oliver E. Craig (Organic Geochemistry, 2026)

Protocol development for an efficient digitization of palaeontological heritage: The case of Camp dels Ninots fossil site (Spain) - Adriana Linares-Martín; Bruno Gómez de Soler; Roy M. Farman; Elena Moreno-Ribas; Pablo Mateos Prieto; Marta Fontanals; Andrea Alías; Javier Sopesens; Hugues-Alexandre Blain; Gerard Campeny Vall-llosera (Geoheritage, 2026)

Evaluating soil communities sensibility to forest structure through the use of eDNA metabarcoding and the Index of Biodiversity Potential - Alexandre Raimbault; Mélanie Roy; Coralie Roy-Camille; Jean-Marie Savoie; Nicolas Gouix; Laurent Larrieu; Antoine Brin (Forest Ecology and Management, 2026)

Quantitative summary of nine years of fungicide efficacy data for managing white spot and protecting yield in maize - MonalisaC. De Cól; Karla Braga; AdrianoA.P. Custódio; Marcelo G. Canteri; Lucas H. Fantin; Carlos M. Utiamada; Hércules D. Campos; Dagma D. Silva-Araújo; Rodrigo V. Costa; InêsF.U. Yada; Aildson P. Duarte; Alfredo R. Dias; et al. (Crop Protection, 2025)

Bacterial and nematode communities associated with soybean-cultivated soils from two native Brazilian biomes - Felipe Martins do Rêgo Barros; Roy Neilson; Madeline Giles; Sandra Caul; Alexandre Pedrinho; Claudio Marcelo Gonçalves de Oliveira; Luiz Antônio da Silva; Victor Lucas Vieira Prudêncio de Araújo; Lucas William Mendes; Fernando Dini Andreote (Applied Soil Ecology, 2025)

Dust transport pathways from the Mesopotamian Marshes - Hesam Salmabadi; Mohsen Saeedi; Michael Notaro; Alexandre Roy (Aeolian Research, 2025)

Influence of vegetative cover on snowpack mercury speciation and stocks in the greening Canadian subarctic region - Maëlys Bockhoff; Holly Marginson; Henry Ittulak; Alexandre Roy; Marc Amyot (Environmental Research, 2025)

Pervasive transcription of plant organelle genomes: functional noncoding transcriptomes? - Matheus Sanita Lima; Alexandre Rossi Paschoal; Douglas Silva Domingues; David Roy Smith (Trends in Plant Science, 2024)

NMR- and HRMS-based untargeted metabolomic study of metal-stressed Euglena gracilis cells - Asma Farjallah; Alexandre Roy; Céline Guéguen (Algal Research, 2024)

Quantifying the contribution of Middle Eastern dust sources to PM10 levels in Ahvaz, Southwest Iran - Hesam Salmabadi; Mohsen Saeedi; Alexandre Roy; Dimitris G. Kaskaoutis (Atmospheric Research, 2023)

Novelties in Lactifluus subg. Gymnocarpi (Russulales, Basidiomycota) from Brazilian tropical forests - Alexandre G. S. Silva-Filho; Mariana C. A. Sá; Dirce L. Komura; Iuri G. Baseia; Paulo Marinho; Jean-Marc Moncalvo; Mélanie Roy; Felipe Wartchow (Mycological Progress, 2021)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Evaluating ENSO teleconnections using observations and CMIP5 models - Indrani Roy; Alexandre S. Gagnon; Devendraa Siingh (Theoretical and Applied Climatology, 2019)

Mapping of novel salt tolerance QTL in an Excalibur × Kukri doubled haploid wheat population - Muhammad A. Asif; Rhiannon K. Schilling; Joanne Tilbrook; Chris Brien; Kate Dowling; Huwaida Rabie; Laura Short; Christine Trittermann; Alexandre Garcia; Edward G. Barrett-Lennard; Bettina Berger; Diane E. Mather; et al. (Theoretical and Applied Genetics, 2018)
Key message Novel QTL for salinity tolerance traits have been detected using non-destructive and destructive phenotyping in bread wheat and were shown to be linked to improvements in yield in saline fields. Abstract Soil salinity is a major limitation to cereal production. Breeding new salt-tolerant cultivars has the potential to improve cereal crop yields. In this study, a doubled haploid bread wheat mapping population, derived from the bi-parental cross of Excalibur × Kukri, was grown in a glasshouse under control and salinity treatments and evaluated using high-throughput non-destructive imaging technology. Quantitative trait locus (QTL) analysis of this population detected multiple QTL under salt and control treatments. Of these, six QTL were detected in the salt treatment including one for maintenance of shoot growth under salinity ( QG (1 – 5) .asl - 7A ), one for leaf Na + exclusion ( QNa.asl - 7A ) and four for leaf K + accumulation ( QK.asl - 2B.1 , QK.asl - 2B.2 , QK.asl - 5A and QK:Na.asl - 6A ). The beneficial allele for QG (1 – 5) .asl - 7A (the maintenance of shoot growth under salinity) was present in six out of 44 mainly Australian bread and durum wheat cultivars. The effect of each QTL allele on grain yield was tested in a range of salinity concentrations at three field sites across 2 years. In six out of nine field trials with different levels of salinity stress, lines with alleles for Na + exclusion and/or K + maintenance at three QTL ( QNa.asl - 7A , QK.asl - 2B.2 and QK:Na.asl - 6A ) excluded more Na + or accumulated more K + compared to lines without these alleles. Importantly, the QK.asl - 2B.2 allele for higher K + accumulation was found to be associated with higher grain yield at all field sites. Several alleles at other QTL were associated with higher grain yields at selected field sites.

Genetic interaction between two insulin-dependent diabetes susceptibility loci, Idd2 and Idd13, in determining immunoregulatory DN T cell proportion - Roxanne Collin; Kathy Doyon; Victor Mullins-Dansereau; Martin Karam; Geneviève Chabot-Roy; Erin E. Hillhouse; Alexandre Orthwein; Sylvie Lesage (Immunogenetics, 2018)

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

Secondary succession impairment in restored mangroves - André Scarlate Rovai; Eduardo Juan Soriano-Sierra; Paulo Roberto Pagliosa; Gilberto Cintrón; Yara Schaeffer-Novelli; Ricardo Palamar Menghini; Clemente Coelho-Jr; Paulo Antunes Horta; Roy R. Lewis; José Carlos Simonassi; Jonatha Alexandre Andrade Alves; Flávio Boscatto; et al. (Wetlands Ecology and Management, 2012)

Comparative study of the interaction of fullerenol nanoparticles with eukaryotic and bacterial model membranes using solid-state NMR and FTIR spectroscopy - Patrick P. Brisebois; Alexandre A. Arnold; Yoann M. Chabre; René Roy; Isabelle Marcotte (European Biophysics Journal, 2012)

Simulation hydrologique des derniers jours de la crue de printemps: le problème de la neige manquante - Richard Turcotte; Thomas-Charles Fortier Filion; Pierre Lacombe; Vincent Fortin; Alexandre Roy; Alain Royer (Hydrological Sciences Journal, 2010)

Non-invasive conservation genetics of the critically endangered golden-crowned sifaka (Propithecus tattersalli): high diversity and significant genetic differentiation over a small range - Erwan Quéméré; Edward E. Louis; Alexandre Ribéron; Lounès Chikhi; Brigitte Crouau-Roy (Conservation Genetics, 2010)